2020
DOI: 10.3390/cancers12092394
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER3, a Catalytically Defective Receptor Tyrosine Kinase, Prevents Resistance of Lung Cancer to a Third-Generation EGFR Kinase Inhibitor

Abstract: Although two growth factor receptors, EGFR and HER2, are amongst the best targets for cancer treatment, no agents targeting HER3, their kinase-defective family member, have so far been approved. Because emergence of resistance of lung tumors to EGFR kinase inhibitors (EGFRi) associates with compensatory up-regulation of HER3 and several secreted forms, we anticipated that blocking HER3 would prevent resistance. As demonstrated herein, a neutralizing anti-HER3 antibody we generated can clear HER3 from the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Clinical trials should determine the mode and duration of citrate sodium administration, its toxicity, and its efficiency. Knowing that numerous patients worldwide have incurable cancers supported by aerobic glycolysis and key oncogenic drivers (such as IGF-1R, Ras/PI3K/Akt, HER2/neu, WNT/β-catenin, TME acidity and EMT) [ 145 , 161 , 162 ], all pathways efficiently counteracted by citrate sodium in preclinical studies, we strongly believe that the citrate strategy we have proposed since many years [ 25 ] should now be considered for clinical trials. In particular, this strategy could increase both the sensitivity to standard chemotherapy drugs and to targeted therapies, whose resistance is mainly supported by the Warburg effect and its oncogenic drivers.…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Clinical trials should determine the mode and duration of citrate sodium administration, its toxicity, and its efficiency. Knowing that numerous patients worldwide have incurable cancers supported by aerobic glycolysis and key oncogenic drivers (such as IGF-1R, Ras/PI3K/Akt, HER2/neu, WNT/β-catenin, TME acidity and EMT) [ 145 , 161 , 162 ], all pathways efficiently counteracted by citrate sodium in preclinical studies, we strongly believe that the citrate strategy we have proposed since many years [ 25 ] should now be considered for clinical trials. In particular, this strategy could increase both the sensitivity to standard chemotherapy drugs and to targeted therapies, whose resistance is mainly supported by the Warburg effect and its oncogenic drivers.…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…Our previous studies showed that treatments of erlotinib‐resistant models with an anti‐EGFR antibody evoke a compensatory response that up‐regulates two EGFR family members, HER2 and HER3 (Mancini et al, 2015). Hence, we combined a TKI and mAbs against EGFR/HER‐family members and observed effective inhibition of erlotinib‐resistant tumors in cell line xenografts (Mancini et al, 2015; Mancini et al, 2018; Romaniello et al, 2018; Romaniello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Through similar mechanisms, the combination of a neutralizing anti-HER3 antibody that can clear HER3 from the cell surface, with osimertinib and cetuximab generated similar results. 55 These studies thus further underline the importance of targeting MEK/ERK pathway in preventing and overcoming acquired resistance to osimertinib.…”
Section: Introductionmentioning
confidence: 89%